Modelo de mecanismo de ruptura da vertente pelas descontinuidades hidráulicas em latossolo no sítio urbano de Santa Teresa/ES - Barreto, Nara Rodrigues (2016)
The diagnosis of the slope stability is to identify breaks, from research conditioning factors, considering water and hydraulic conductivity important agents that enhance the mechanisms break from the slopes. The objective of this research is the ratio of saturated hydraulic conductivity (Ksat) in Oxisols with the stability condition of the urban arm of the Vila Nova neighborhood, Santa Teresa (Espírito Santo, Brazil), through integrated analysis of topographic subdivision surface structure and landscape physiology, emphasizing the soil characteristics, geomorphological and hydrodynamic. hypsometry bases, slope and drainage density were generated for a mass movement susceptibility model as a preliminary approach to possible discontinuities in the hydraulic urban area of Santa Teresa. The morphological description of the soil was held in soil upstream of a strand subjected to roadblock. For characterization and definition of soil class by the Brazilian System of Soil Classification, a sample of the Bw horizon was collected and thin dry land to air (TFSA) certain Fe2O3, Al2O3 and SiO2 by sulfuric attack, K and Na Mehlich-1 extractor , Ca² +, Mg² + Al³ + extractor KCl 1 mol / L, H + Al extractor Calcium acetate 0.5 mol / L - pH 7.0. Samples were collected for physical, in the depths of 0,20; 0,40; 1,00 and 1,80 m, corresponding to Ap horizons, Bw1, Bw2 and C. Samples of the TFSA received pre-treatment with chemical dispersion with NaOH and physical dispersion in slow agitation, and Particle size analysis was conducted by the method of the pipette. The bulk density was obtained by the volumetric ring method and macro, micro and total porosity by voltage table method. Saturated hydraulic conductivity (Ksat) at constant load, was held in undisturbed sample volumetric ring, obtained by Darcy law. For determining the water retention curve in the soil tests were carried out in tension table, using pressures of 6 to 10 (soil samples of volumetric ring), and testing in Richards chamber, using voltages of 30, 300 and 1500 kPa (samples deformed). The horizon C Latossol below 240 cm was analyzed with the operation of the GPR (ground-penetrating radar), to identify breakages. The results of morphological and soil chemical analysis pointed to the class definition (SiBCS) of Red-Yellow Oxisols typical Dystrophic, and predominantly kaolinitic mineralogy and oxidic. The hydraulic conductivity tests and retention curves show the existence of a hydraulic discontinuity at 180 cm depth between Bw2 and C horizons, corresponding to a water behavior that leads to the development of the positive pore pressure and soil suction loss here attributed to the following conditioning factors: the passage of a pedological aggregate structure weak and microaggregates subangular blocks (small grain) on the horizon Bw1 and predominantly microaggregates pedologic aggregates in Bw2 horizon due to kaolinitic mineralogy and oxidic clay fraction to a degree of coherent massive structure on the horizon C; and reducing the clay content and increase in the silt content in the horizon C. The images derived from surveys with georadar onstrated the existence of breaking plans due to deformation of the material in the horizon C. The water discontinuity observed in Latossolo shows the decrease and the change of direction of fluid flow in the subsurface, from vertical to horizontal at this limit, which may lead to the formation of a subsuperfiaial break up and establishment of instability in the shed.